La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Jumol-Julia Edéry’s Wedding in Early 20th Century Morocco - Cohen, Judith R. (Canadian Jewish Studies/Études juives canadiennes, 2022)

"If you see me walking alone on the road": Sephardic Songs of Exile, Expulsion, Memory – and Return - Cohen, Judith R. (Armenian and Jewish Experience between Expulsion and Destruction, 2021)

Socialisation musicale et sociabilités urbaines. Parcours de personnes immigrantes originaires d'Afrique du Nord à Montréal - Marcoux-Gendron, Caroline (L'interculturel contemporain au carrefour des disciplines, 2021)

Bïa Krieger versionista: Três cançoes de Chico Buarque em francês [Bïa Krieger, versionista. Trois chansons de Chico Buarque en français] - Cassiano, Raissa Conde (Université de São Paulo, 2020)

L'adaptation de chanson dans l'album ”Cœur vagabond” de Bïa. Une brise de Brésil - Abbrugiati, Perle (ATeM – Archiv für Textmusikforschung, 2019)
Perle Abbrugiati's article explores Coeur vagabond/Coraçao vagabundo, the fourth record by the French-Brazilian artist Bïa, released in 2006. The bilingual album comprises an equal number of Brazilian-Portuguese adaptations from French songs and French adaptations from Brazilian songs. The aim of the present article is to identify the strategies applied in the translation of songs. To this end, the article's author herself uses translation within the framework of a comparative approach, confronting Bïa's translations with her own literal translations (not suitable to be sung) of the original lyrics. The objective is not to trace 'mistranslations' but to point out in how many different and intricate ways a translation can be faithful while being creative, and in what way and to what degree the song translator may take the liberty of 're-semantisation'.
Keywords: Chanson; traduction

“Portrait en Noir et Blanc”: Chico Buarque em francês por Bïa Krieger [“Portrait en Noir et Blanc”: Chico Buarque en français par Bïa Krieger] - Cassiano, Raissa Conde (Tradução em Revista, 2019)

Lhasa de Sela et la traversée des espaces - Proulx, Robert (Archiv für Textmusikforschung, 2018)
The singer-songwriter Lhasa de Sela (1972-2010) launched her career and produced her three records in Montreal where she arrived in 1991. Not only did she change the face of migrant song in Quebec, but she also enjoyed international success, embarking on long world tours and selling more than a million records. This analysis will focus on the songs from her second album, The Living Road, and will show that Lhasa de Sela transcended linguistic and artistic frontiers by crossing the geographical border when she made Montreal her home and creative hub.

Java to Jazz: Eva Gauthier - Spiller, Henry (Javaphilia: American Love Affairs with Javanese Music and Dance, 2015)

Auditeurs en exil : le cas des Chiliens à Montréal et leur rapport à deux chansons emblématiques - Gonzalez, Laura Francisca Jordán (Volume !. La revue des musiques populaires, 2013)
Cet article examine l’expérience des auditeurs chiliens exilés à Montréal, se concentrant spécifiquement sur leurs écoutes pendant la dictature militaire (1973-1989). Issus d’une méthodologie mixte qui combine l’histoire orale et l’analyse musicale, les résultats de cette recherche musicologique révèlent la place primordiale que l’audition musicale eut chez les exilés dans la reconstruction d’un lien avec leur pays d’origine, ainsi que dans le développement du mouvement de solidarité avec le peuple chilien. L’article explique, d’abord, le déploiement des goûts musicaux et identifie les répertoires canoniques qui demeurent au centre des écoutes. Ensuite, il aborde le rôle de l’usage des enregistrements en vinyle et cassette, et de la radio dans la diffusion des musiques. Enfin, les deux dernières sections explorent les significations associées aux pièces musicales ‘Gracias a la Vida’ et ‘Vuelvo’, mettant en relief la complexité de la réception en ce qui concerne la construction des identités culturelles, le récit des histoires personnelles et communautaires.
Keywords: bootleg / piratage / contrefaçon; cassette / bande magnétique; communautés / minorités; migration / diaspora / exil; réception; écoute / auditeur

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.

Polyrhythmic Dance Currents: Race Multiculturalism and the Montreal Dance Community - Templeton, Melissa (Université de Californie à Riverside, 2012)

Selanikli Humour in Montreal: the Repertoire of Bouena Sarfatty Garfinkle (1916-1977) - Cohen, Judith R. (Judeo Espaniol: Textos satíricos judeoespañoles: de salonicenses o sobre salonicenses/Satirical Texts in Judeo-Spanish by and about the Jews of Thessaloniki, 2011)

La musique des Chiliens exilés à Montréal pendant la dictature (1973-1989) : la création de musiques de la résistance politique et la réception des auditeurs dans l’exil - Jordan Gonzalez, Laura Francisca (Université de Montréal, 2011)
Cette étude musicologique aborde la musique pratiquée et écoutée par les Chiliens exilés à Montréal pendant la dictature (1973-1989), se concentrant sur l’histoire de la musique du point de vue des auditeurs. Quelles musiques participent à l’expérience d’exil et quel rôle accomplissent-elles? Comment les musiques accompagnent-elles le processus d’adaptation au pays d’accueil et comment aident-elles à construire un lien avec le pays d’origine? Ce sont quelques unes des questions qui ont guidé le développement de la recherche, dont la méthodologie est mixte et se concentre sur l’entrevue. Trois dimensions de l’histoire musicale y sont examinées. Premièrement, la contribution de la pratique musicale au mouvement de solidarité envers le peuple du Chili, notamment à travers la formation d’ensembles musicaux et l’organisation des peñas et des concerts. Deuxièmement, le rôle des musiques dans la construction d’une communauté culturelle chilienne, où différents discours sur l’identité nationale et politique sont négociés. Troisièmement, la présence des musiques dans les expériences individuelles d’exil, de déracinement et d’adaptation. Les genres de musique populaire les plus présents, soit la Nueva Canción Chilena et la Proyección Folclórica, ainsi que leurs enjeux des significations identitaires et politiques, font partie de la problématique du présent texte. La cueca, considérée la danse nationale, occupe aussi une place privilégiée de la discussion, due à la place importante qu'elle occupe dans la communauté chilienne de Montréal.

"Si mosós no las vamos a recoger...": The Songbooks of Emily Sene and Bouena Sarfatty-Garfinkle - Havassy, Rivka (Los sefardíes ante los retos del mundo contemporáneo. Identidad y mentalidades [Les sépharades face aux défis du monde contemporain. Identité et mentalités], 2010)

Interpreting success and failure: the eclectic careers of Eva and Juliette Gauthier - Slominska, Anita (Université McGill, 2009)
My dissertation explores the eclectic singing careers of sisters Eva and Juliette Gauthier. Born in Ottawa, Eva and Juliettte were aided in their musical aspirations by the patronage of Prime Minister Wilfred Laurier and his wife Lady Zoë. They both received classical vocal training in Europe. Eva spent four years in Java. She studied the local music, which later became incorporated into her concert repertoire in North America. She went on to become a leading interpreter of modern art song. Juliette became a performer of Canadian folk music in Canada, the United States and Europe, aiming to reproduce folk music “realistically” in a concert setting. My dissertation is the result of examining archival materials pertaining to their careers, combined with research into the various social and cultural worlds they traversed. Eva and Juliette’s careers are revealing of a period of transition in the arts and in social experience more generally. These transitions are related to the exploitation of non-Western people, uses of the “folk,” and the emergence of a cultural marketplace that was defined by a mixture of highbrow institutions and mass culture industries. My methodology draws from the sociology of art and cultural history, transposing Eva and Juliette Gauthier against the backdrop of the social, cultural and economic conditions that shaped their career trajectories and made them possible.

Tunes That Bind: Paul J. Seelig, Eva Gauthier, Charles T. Griffes, and the Javanese Other - Spiller, Henry (Journal of the Society for American Music, 2009)
The powerful concept of orientalism has undergone considerable refinement since Edward Said popularized the term with his eponymous book in 1978. Orientalism typically is presented as a totalizing process that creates polar oppositions between a dominating West and a subordinate East. U.S. orientalisms, however, reflect uniquely North American approaches to identity formation that include assimilating characteristics usually associated with the Other. This article explores the complex relationship among three individuals—U.S. composer Charles T. Griffes, Canadian singer Eva Gauthier, and German-trained Dutch East Indies composer Paul J. Seelig—and how they exploited the same Javanese songs to lend legitimacy to their individual artistic projects. A comparison of Griffes's and Seelig's settings of a West Javanese tune (“Kinanti”) provides an especially clear example of how contrasting approaches manifest different orientalisms. Whereas Griffes accompanied the melody with stock orientalist gestures to express his own fascination with the exotic, Seelig used chromatic harmonies and a chorale-like texture to ground the melody in the familiar, translating rather than representing its Otherness. The tunes that bind Griffes, Gauthier, and Seelig are only the raw materials from which they created their own unique orientalisms, each with its own sense of self and its own Javanese others.

Three Canadian Sephardic Women and their Transplanted Repertories: From Salonica, Larache and Sarajevo to Montreal and Kahanawá:ke - Cohen, Judith R. (Folk Music, Traditional Music, Ethnomusicology: Canadian Perspectives Past and Present, 2007)

The Ladino Song in the 20th Century: A Study of the Collections of Emily Sene and Bouena Sarfatty-Garfinkle - Havassy, Rivka (Université Bar-Ilan, 2007)
Keywords: Pas de lien web

La rencontre des musiques du Moyen-Orient et de l'Occident : esthétisme, composition et analyse - Makdissi-Warren, Katia (Université de Montréal, 2007)
The object of this dissertation is the meeting of Middle-Eastern and Western music. The dissertation includes an essay and seven original compositions (scores and recordings). The text begins with the exposition of the basics of Middle-Eastern music required to understand my artistic approach. The 'taqasim', a major musical form in the Middle-East and a source of inspiration for my work is presented in more detail. The second chapter deals with the philosophy of aesthetics involved in the intermixing of musical cultures. Concerns about the coherence of commingled languages are exposed. The concepts of intermixing, cultural identity and coherence of a work are submitted for discussion. For a given work, does the notion of coherence retain its essence from one person to the next according to culture and social context? This questioning is directly linked to the creation and generation of the processes of development for the musical material in my compositions. Throughout the chapter, I position my approach in relation to the thinking of authors such as Adorno, but also relative to personal experiences. In chapter 3 I describe the writing processes I have developped in order to create a sound fabric wherein Middle-Eastern music meets that of the West. My work defines processes for treating parameters in order to draw together elements of both Eastern and Western musical expressions into a distinctive language <f> <fr><nu>.</nu><de>7</de></fr></f> the key to this is grasping how one musical element influences another. Using analysis as a starting point for the comparison of musical parameters in each of the languages, I have elaborated new commingling (intermixing) techniques. This chapter is therefore devoted to the cross-relational writing techniques that have been evolved to adequately support my artistic approach. The final chapters of this dissertation feature the detailed analyses of three of my compositions: 'Jet Stream, Algorythme and PLB'. Each piece's form, sections and sub-sections are presented followed by the analysis of its basic musical material and development.

The Memoirs of a Partisan from Salonika - Melammed, Renee Levine (Nashim: A Journal of Jewish Women's Studies & Gender Issues, 2004)

A Bosnian Sephardic Woman in Kahnewake, Quebec - Cohen, Judith R. (Canadian Woman Studies/Les cahiers de la femme, 1996)

Women's Roles in Judeo-Spanish Song Traditions - Cohen, Judith R.; Sacks, Maurie (Active Voices: Women in Jewish Culture, 1995)

Sierra norteña: The influence of Latin music on the French-Canadian popular song and dance scene, especially as reflected in the career of Alys Robi and the pedagogy of Maurice Lacasse-Morenoff - Sévigny, Jean-Pierre (Productions Juke-box, 1994)

Expressive Modes in the Judeo-Spanish Wedding Song - Anahory-Librowicz, Oro (New Horizons in Sephardic Studies, 1993)

The Music of the Songs: Musical Transcriptions and Commentary of the Songs Discussed by Oro Anahory-Librowicz "Expressive Modes in the Judeo-Spanish Wedding Song" - Cohen, Judith R. (New Horizons in Sephardic Studies, 1993)

Women and Judeo-Spanish Music - Cohen, Judith R. (Bridge, 1993)

The Odyssey of Dahlia Obadia: Morocco, Israel, Canada - Sawa, Suzanne Myers (Canadian Folk Music Journal, 1991)
Dahlia Obadia interprète les danses de la tradition du moyen orient. Pendant sa carrières, elle a rémarque qu’il existe des grandes différences entre les interprétations de cette tradition vue de l’intérier et de l’extérieur. L’auteur décrit la vie de Dahlia et explore les problèmes qu’elle a affrontes pendant sa quête de sa propre identité culturelle.

"Ya salio de la mar": Judeo-Spanish Wedding Songs among Moroccan Jews in Canada - Cohen, Judith R. (Women and Music in Cross-Cultural Perspective, 1989)

Cancionero Séphardi du Québec - Anahory-Librowicz, Oro (Cégep du Vieux Montréal, 1988)